Implementation of IFRSs and IFRS for SMEs: the case of Estonia - Lehte Alver; Jaan Alver; Liis Talpas (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This paper gives an overview of prior writings published by Estonian researchers that have analyzed the development of Estonian accounting legislation and financial reporting and potentially contributes to the understanding of Estonian international financial reporting standards' implementation issues. The authors have analyzed the history of Estonian accounting legislation from 1990 until 2013 and have divided the integration of Estonian accounting system to the framework of IFRSs into two stages: 1) implementation of IFRSs, and 2) implementation of the IFRS for SMEs. The paper also analyzes the possible changes the new European Union Accounting Directive will bring to the Estonian accounting framework. As a methodological technique literature review and document analysis are used, including bachelor and master thesis and papers written by the Estonian researchers. In conclusion, it may be said that the implementation of IFRSs and IFRS for SMEs in the form of the Estonian good accounting practice (EGAP) has been smooth and successful in Estonia.
Keywords: M41; 650; Estonia; implementation of IFRS; implementation of IFRS for SMEs; new EU Accounting Directive